Stealth and Designer Citrobacter Fruendii Vaccines - Ibrahim Mohamed Saeed Shnawa (Vaccines and Vaccine Interference, 2023)
Citrobacter freundii are currently constitute…the position of an emerging human pathogen.Several vaccine versions are tempted, of which stealth vaccine version and designer vaccine versions,at the level of laboratory development both of these versions are pure ,safe,antigenic and immunogenic.